Customer Satisfaction Index of Singapore 2010: Full Year Overview - Institute of Service Excellence, SMU (Institutional Knowledge at Singapore Management University, 2011)
The Customer Satisfaction Index of Singapore (CSISG) has completed its fourth consecutive year of measurement since 2007. Under a quarterly measure and release system with two out of eight sectors measured per quarter, CSISG 2010 scores of companies for the Retail and Info-Communications sectors were released in the first quarter of 2010, Transportation & Logistics and Education sectors released in the second quarter, Food & Beverage and Tourism sectors released in the third quarter, and finally the current release of Finance & Insurance and Healthcare sectors, marking the end of measurement for 2010. The CSISG 2010 national score is computed using all the data collected over the past year. CSISG scores are generated based on the econometric modeling of survey data collected from end-users after consumption of products and services. Sub-sector scores are defined as weighted averages of company scores, with the weights being proportional to revenue contribution of the companies within each sub-sector. Sector scores are defined similarly, aggregating the sub-sector scores proportionately to each sub-sector’s revenue contribution. Finally, the national score is weighted according to each sector’s contribution to GDP. CSISG scores customer satisfaction on a scale of 0 to 100 with higher scores representing better performance.